The Influence of Work Discipline, Organizational Culture, and Work Conflict on Employee Performance: A Study of Miss Cimory Employees at Cimory Center Pesanggrahan - Hendrawan, Koen; Ibrahim, Rizqi Maulana; Kuncoro, Aris Wahyu; Wahyudi, Widi (Jurnal Multidisiplin Sahombu, 2025)
This study aims to examine the influence of work discipline, organizational culture, and work conflict on employee performance. The research was conducted on employees of Miss Cimory at Cimory Center Pesanggrahan. A quantitative approach was employed using a questionnaire distributed to the respondents. The data were analyzed using multiple linear regression with the assistance of statistical software. The findings indicate that work discipline does not have a significant effect on employee performance. In contrast, organizational culture shows a positive and significant influence, suggesting that a strong and supportive organizational culture can enhance employee performance. Furthermore, work conflict also has a significant effect, which implies that certain forms of conflict may act as stimulants to employee productivity when managed properly. These results provide valuable insights for organizational leaders in developing strategies to improve employee performance by fostering a positive culture and managing conflict effectively.